Knowledge of dengue hemorrhagic fever (DHF) prevention as a protective factor for psychological well-being in elementary school students - Kertiyasa, I Nyoman Danu; Resiyanthi, Ni Komang Ayu; Mirayanti, Ni Ketut Ayu (JOURNAL OF Mental Health Concerns, 2026)
Background: Dengue Hemorrhagic Fever (DHF) is an infectious disease that remains a public health problem in Indonesia, especially in tropical regions. Elementary school-aged children are among the groups vulnerable to dengue fever transmission, so adequate knowledge regarding early prevention efforts is needed. Schools have an important role as a means of health education to shape dengue fever prevention behavior in students. Purpose: To analyze the level of knowledge regarding Dengue Hemorrhagic Fever (DHF) prevention among students. Method: This study used a quantitative descriptive design with a cross-sectional approach. The study population was all 80 students in grades III–VI, with a sample of 67 respondents selected using a purposive sampling technique. Data collection was carried out using a questionnaire regarding the level of knowledge of dengue fever prevention, then analyzed using univariate analysis to determine the frequency distribution and percentage. Results: The results showed that most of the respondents were aged 12 years (32 students (47.8%) and the majority were female (43 students (64.2%). The level of student knowledge regarding dengue fever prevention was dominated by the sufficient category with 44 respondents (65.7%), followed by the good category with 18 respondents (26.9%), and the poor category with 5 respondents (7.5%). Conclusion: Student knowledge regarding dengue fever prevention is already there but is not optimal, so efforts are needed to improve health education in a sustainable and structured manner in the school environment to improve understanding and behavior in dengue fever prevention among elementary school students. Keywords: Dengue Fever Prevention; Dengue Hemorrhagic Fever; Level of Knowledge.